Gastronomy Game Board Project Based Learning in Higher Education - Pratiwi, Ilma Indriasri; Suwandi, Andreas; Khaerani, Rijal; Fauzan, Hilma Azahra (Journal of Tourism Education, 2021)
The project-based learning approach is an effort to eliminate student boredom in learning during the Covid-19 pandemic. Project-based learning or known as project-based learning is learning that trains students to get hands-on experience through learning media that is adapted to the material in the syllabus. The purpose of this study was to determine the effect of the project-based learning model on the evaluation and learning achievement of students in the knowledge of materials, tools and cooking methods class aimed at tourism education students who contracted this course. The data collection method in this study was observational data and surveys using a questionnaire. With 37 questions distributed via google form to 4th semester tourism education students randomly as respondents. The survey results show that there is a strong influence of the project-based learning model on the achievement of lecture learning. It is also known that project-based learning is able to increase student involvement in group work and original thinking in project development carried out during learning.